A Holistic Model for Making Cloud Migration Decision: A Consideration of Security, Architecture and Business Economics - Johnson, B.; Yanzhen Qu (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
The emergence of cloud computing services has created an additional dimension in the decision for creating a new business plan which requires computing resources. Although quite a few of the recent published analytical models have provided some very good ground work for assessing the cost difference between in-house systems and leasing cloud services for the same set of computing requirements, there is a need for research towards providing a company with risk analysis tools that will allow business managers to assess the viability of migrating business applications to the cloud with broader considerations. This article consolidates several genres of analysis on cloud computing risk. We derive an new analytical model that takes into account business economics, and other business requirements such as various considerations on security and availability. This model applies these considerations to the already well researched buy-or-lease models currently used by business management professionals which allows for an easy transition to this more thorough model. We made a comparison research through evaluating the service requirement situation from published research against two service providers. The results of this research demonstrates the veracity of our model. The rationale for this research is to provide a more complete and robust model that encompasses the entire spectrum of considerations yet holds a high degree of precision.